Development and Implementation of Profile Videos as an Effective Promotion Media for Al-Azhar Batam Vocational School - Jeffrey Rustandi (Universitas Internasional Batam, 2024)
School competence becomes one of the factors influencing students' desire to continue their education. A new profile video can provide an overview of the school's competence and advantages, making both students and parents more interested. The educational institution, SMK Al-Azhar Batam, is grounded in Islamic knowledge and practices. It was founded on July 2, 2002, and is a private educational institution managed by the Al-Azhar Batam Islamic Foundation.I conducted a Community Service (PKM) activity with SMK Al-Azhar Batam, which involved creating a new profile video for the school. The video aims to showcase the school's competence and strengths based on a storyboard and video concept developed through qualitative data collection using observations and interviews. The video production includes capturing partner video recordings and editing and rendering the video using Adobe Premiere Pro 2022 software, resulting in a new profile video for the partner. The completed profile video will be sent to the partner to be uploaded to the official SMK Al-Azhar Batam YouTube channel.